KONSEP SAKINAH DALAM RUMAH TANGGA PERSPEKTIF AL-RAZI DAN ABRAHAM MASLOW - Ahmad Daniyal; Zainul Muin Husni (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
Peace in the family (sakinah) is the hope of all couples. Creating a sakinah family is not merely the duty of a wife, but must be supported by both parties (husband and wife). Household life will also require several patterns that form the basis of a strong and harmonious family foundation. This pattern will later complement the deficiencies that should exist in the family. During the trip, many families in which there are problems, which are caused by several unfulfilled needs, instead take the way of divorce rather than maintaining family relationships.In Islamic studies literacy, forming a sakinah family can be achieved through the mawaddah and rahmah stages. Al-Razi in his commentary explains that mawaddah means jima 'and rahmah is to have children. Although now this is considered irrelevant by most people, but in an analytic-comparative way, what Al-Razi said above can be supported by a psychological perspective.Abraham Maslow, a well-known humanistic psychologist, explained that in his life, humans must meet their standard of life. There are five patterns of needs that must be met hierarchically. Among them are psychological safety, love / belonging esteem and self-actualization. These five needs will later support the actualization process in humans, as well as in pairs. If the five stages of these needs are met, then humans will get happiness and satisfaction in having a family.